PENGARUH MEDIA VIDEO ANIMASI TERHADAP KETERAMPILAN MENYIMAK DAN BERBICARA SISWA KELAS IV SEKOLAH DASAR - Eko Wahyudi (Jurnal Binagogik, 2025)
This study aims to test the effect of animated video media on the listening and speaking skills of fourth grade elementary school students. This study is a quasi-experimental study and uses a nonequivalent control group design. The population used in this study were all fourth grade students at elementary schools in Sungai Pinang District, Banjar Regency in the odd semester of 2024/2025. This study used a sample of 91 students from Kupang Rejo Elementary School, Pakutik Elementary School, Rantau Nangka Elementary School, and Sungai Pinang Elementary School. The sample used was determined by purposive sampling technique. In this study, there were two types of samples, namely the experimental class and the control class. This study used instruments in the form of descriptive questions and observation sheets. The data that has been collected will be analyzed using the Paired Sample t test and Independent Sample t with a sig. level of 0.05. The results of the study prove that the use of animated video media positively and significantly affects the listening and speaking skills of fourth grade elementary school students